Module 5: Shopping. Clothes. Module 6: Sport: Pre-Intermediate - Intermediate; Class Book; учебное пособие - Анисимова Е. М. Екатерина Михайловна; Ткаченко Л. К. Лариса Константиновна; Панасенко Е. А. Елена Александровна; Соколова Э. Я. Эльвира Яковлевна (General English for Technical students)
Исключено из фонда НТБ ТПУ